Tradisi Penulisan Hadis Syiah dan Sunni: Telaah Perspektif Rasul Ja'fariyan dalam Tadwin al-Hadits - Muhammad; Nur Laili Nabilah Nazahah Najiyah (Journal of Hadith Studies, 2025)
Sunni and Shi'a are among the major Islamic sects that exhibit significant differences in their understanding of the historical development of Hadith, particularly regarding its writing and compilation. The Sunni tradition holds that the formal documentation of Hadith began in the second century of the Hijri calendar. In contrast, Shi’a literature asserts that the writing of Hadith was already practiced during the lifetime of the Prophet Muhammad (peace be upon him). This paper seeks to analyze the historiographical approach to Hadith in Rasul Ja’fariyan’s book Penulisan dan Penghimpunan Hadis (Writing and Compilation of Hadith). Accordingly, the study addresses three main research questions: First, what is the genealogy of Hadith historiography? Second, how is the historicity of Hadith portrayed in both Sunni and Shi’a perspectives within Ja’fariyan’s work? Third, how does Ja’fariyan assess the historical trajectory of Sunni Hadith writing from a Shi’a standpoint? This is a qualitative study that relies on Ja’fariyan’s aforementioned book as its primary source, supported by secondary materials such as scholarly books, journals, and relevant research on the historicity of Hadith in both traditions. The findings reveal three key points. First, the concept of historiography predates the 15th century CE, hence the necessity of documenting Hadith history, referred to as "Hadith historiography," which includes its origins, development, transmission, isnād–matn issues, and compilation periods. Second, Hadith writing became increasingly prominent among Shi’a scholars from the late 3rd century AH, while Sunnis still favored oral transmission. Third, Ja’fariyan critiques Sunni scholars for using Hadith prohibitions on writing to justify what he views as a delayed documentation tradition compared to the Shi’a.